Mobility and Utility in Robot Mediated Interaction: An Interactive Workshop for the Identification of Use Cases and Affordances of Telepresence Robots - Schneiders, Eike; Boudouraki, Andriana; Reyes-Cruz, Gisela; Avila, Juan Pablo Martinez; Elmimouni, Houda; Grønbæk, Jens Emil Sloth; Rintel, Sean; Joshi, Swapna (Mobile HCI 2023, 2023)
In recent years virtual meetings have become the predominant alternative to face-to-face meetings. Ongoing efforts in the design of telepresence robots promise remote access to physical settings and a greater sense of presence, leading to improved remote collaboration. However, a comparable sense of physical presence and utility has yet to be achieved. Mobile telepresence still provides limited ways to interact with remote users (e.g., with the environment and other people). This workshop aims to re-imagine telepresence robots, moving away from the decades-old ‘iPad-on-a-stick’ paradigm. Using interactive activities involving existing telepresence robots and a hybrid workshop format, we hope to ideate ways of expanding the capabilities of mobile telepresence robots through a range of mechanisms (e.g., mobile and wearable technology, Augmented Reality, Internet of Things, etc.) and to inform the future design of these devices to provide additional affordances. In doing so, we plan to identify use cases for which mobile telepresence robots can provide additional value through their locomotive capabilities compared to current screen-based remote interactions. Lastly, we aim to identify scenarios for future research in Mobile HCI using use cases and affordances identified during the workshop to support more equitable participation for remote users.